Prolonged intermittent fever and massive splenomegaly in a miner working in the tropical jungle, China. - Yanbin Liu; Zhiyong Zong (Public Library of Science (PLoS), 2020)
Prolonged fever is a particular challenge. A 47-year-old man with 5-year intermittent fever and remarkable splenomegaly was diagnosed as chronic melioidosis after splenectomy. The case would help clinicians to raise awareness and include chronic melioidosis in the differential diagnosis for patients with the travel history in melioidosis endemic regions.